BLOCKCHAIN APPLICATIONS FOR TRANSPARENCY AND ACCOUNTABILITY IN PUBLIC ADMINISTRATION - Alit Wiliandani (Alqaprint Jatinangor, 2025)
This study explores the growing relevance of blockchain technology as a transformative instrument for enhancing transparency and accountability within public administration. Through a systematic literature review, the research synthesizes findings from recent academic contributions to identify how blockchain’s decentralized, immutable, and verifiable features contribute to reducing corruption and improving trust in governmental processes. The analysis highlights the capacity of blockchain to ensure data integrity, facilitate traceable transactions, and strengthen citizen engagement through open governance mechanisms. Furthermore, the review uncovers critical challenges such as technological readiness, regulatory uncertainty, and institutional resistance that hinder widespread adoption. Comparative studies across countries demonstrate varying levels of success depending on governance maturity and digital infrastructure. The paper also examines theoretical implications for public sector innovation and the reconfiguration of administrative accountability frameworks. Findings suggest that blockchain can shift bureaucratic paradigms toward participatory and evidence-based governance. The study concludes by proposing a strategic roadmap for policymakers to integrate blockchain solutions sustainably and ethically in public administration practices.